Simulation of plasma wakefield excitation by a sequence of relativistic electron bunches - Lotov, K.V.; Maslov, V.I.; Onishchenko, I.N.; Svistun, E.N. (Вопросы атомной науки и техники, 2008)
Numerical simulations of plasma wakefield excitation by a long sequence of low-density relativistic electron bunches are performed with hybrid 2.5D code LCODE. For the resonant sequence, wakefields of up to 300 bunches add coherently until the wave nonlinearity comes into play. За допомогою гібридного 2.5-вимірного коду LCODE проведено чисельне моделювання збудження кільватерних полів у плазмі довгою послідовністю релятивістських електронних згустків невеликої густини. Для резонансного ланцюжка кільватерні поля 300 згустків додаються когерентно, поки не стає суттєвою нелінійність хвилі. С помощью гибридного 2.5-мерного кода LCODE проведено численное моделирование возбуждения кильватерных полей в плазме длинной последовательностью релятивистских электронных сгустков небольшой плотности. Для резонансной цепочки кильватерные поля 300 сгустков складываются когерентно, пока существенной не становится нелинейность волны.